Incisional Reinforcement in High-Risk Patients - Feldmann, Timothy F.; Young, Monica T.; Pigazzi, Alessio (Clinics in Colon and Rectal Surgery, 2014)
Hernia formation after surgical procedures continues to be an important cause of surgical morbidity. Incisional reinforcement at the time of the initial operation has been used in some patient populations to reduce the risk of subsequent hernia formation. In this article, reinforcement techniques in different surgical wounds are examined to identify situations in which hernia formation may be prevented. Mesh use for midline closure, pelvic floor reconstruction, and stoma site reinforcement is discussed. Additionally, the use of retention sutures, closure of the open abdomen, and reinforcement after component separation are examined using current literature. Although existing studies do not support the routine use of mesh reinforcement for all surgical incisions, certain patient populations appear to benefit from reinforcement with lower rates of subsequent hernia formation. The identification and characterization of these groups will guide the future use of mesh reinforcement in surgical incisions.
Keywords: incisional reinforcement; mesh reinforcement; wound closure; incisional hernia